What would make them read more? Insights from Western Australian adolescents - Merga, Margaret (Routledge, 2016)
© 2014 National Institute of Education, Singapore. The link between recreational book reading and improved literacy performance is consistently supported by educational research. Increasing engagement in recreational book reading remains imperative for English teachers, though how to best facilitate this in a secondary context is an object of contention, with limited research in this field. The West Australian Study in Adolescent Book Reading explored attitudes and engagement in recreational book reading. Student responses provide valuable insight directly from the target group that can help to shape best practice for adolescent literacy educators. Findings are presented around six key themes, and include strategies for choice, access to attractive and diverse books, time availability, time allocation, concentration and encouragement.